Trends in crime and violence in Papua New Guinea - Lakhani, Sadaf; Willman, Alys M. (World Bank, Washington, DC, 2014)
Crime and violence are widely viewed as posing a considerable challenge to development in Papua New Guinea (PNG). The full scale of crime and violence in PNG is difficult to assess, given the scarcity of national-level studies and a distinct urban bias in the available studies. Yet various commentators and surveys estimate that violence victimization rates in PNG are among the highest in the world. This briefing note presents some preliminary findings regarding the prevalence of crime and violence in PNG. It was prepared as part of a broader study to understand the socioeconomic costs of crime and violence to businesses, government agencies, Civil Society Organizations (CSOs) and households in PNG. The different data sources reviewed and the most significant challenges with the data available are noted in Annex 1. The challenges in partial data and questions concerning the methodology used for collecting and collating some of the data sets and data integrity call for some caution in interpreting the findings, in particular making generalizations about the wide diversity of provincial experiences on the basis of geographically limited data sets.